Modeling of HTTP Request with Regular Expression for Slow HTTP DoS Attack Detection - nfn Ramlan; Avinanta Tarigan (BBPSDMP KOMINFO MAKASSAR, 2019)
The availability of Web Service is the most important thing to be guaranteed, but there are many threats to the Web Service particularly from the internet, one of the famous methods is Slow HTTP DoS Attack. There are many research projects about this topic before, but there is always the possibility to increase the accuracy rate and minimizing the False Positive Rate and should be considered to use it at the small and medium scale of network infrastructure. In this research, another IDS method was used to find a better result for Slow HTTP DoS Attack detection through modeling HTTP Request based on Regular Expression. Detection patterns made from HTTP Request Traffic of some popular Web Browsers then looked for the similarity of the HTTP Request Traffic using Needleman Wunsch algorithm. This pattern was negated at the important part of HTTP Request headers, then converted to Regular Expression. New Pattern in Regular Expression was inserted to the L7-Filter that part of Netfilter. This method has been proved to detect Slow HTTP DoS Attack with 100% accuracy and False Positive Rate 0%.